Repetition and difference in nature: reinterpreting plants pattern mechanism structure through installation art - Chin, Anna Chui Han (Tanjong Malim, 2022)
Repetition and difference in nature: reinterpreting plants pattern mechanism structure through installation art by Chin, Anna Chui Han